2004
DOI: 10.1080/j.1440-1665.2004.02124.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Running a Trauma and Dissociation Unit: A Contemporary Experience

Abstract: Despite the challenges associated with significant difficulties in the corporate management of a private health-care system, it has been possible to operate an inpatient and day hospital programme tailored to the needs of patients in the dissociative spectrum, and the lessons learnt from this experience are valid considerations in the future planning of mental health services overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As evidenced by the demographic data that showed that 32% of participants were diagnosed with DID by a professional counselor, professional counselors appear to play a significant role in the diagnosis and treatment of clients with DID. Treating individuals with DID often comes with many complicating factors, including long‐term treatment, boundary issues, and co‐occurring disorders (Brand et al, ; Chu, ; Middleton & Higson, ). Thus, gathering as much information about the client as possible may be helpful in navigating complex treatment issues as they arise.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by the demographic data that showed that 32% of participants were diagnosed with DID by a professional counselor, professional counselors appear to play a significant role in the diagnosis and treatment of clients with DID. Treating individuals with DID often comes with many complicating factors, including long‐term treatment, boundary issues, and co‐occurring disorders (Brand et al, ; Chu, ; Middleton & Higson, ). Thus, gathering as much information about the client as possible may be helpful in navigating complex treatment issues as they arise.…”
Section: Discussionmentioning
confidence: 99%
“…There are programs described in the literature that offer weekly group sessions combined with individual therapy (e.g., Harvey & Harney, 1997;Mendelsohn, Zachary & Harney, in press) and outpatient day programs that are combined with hospital inpatient programs (Middleton & Higson, 2004;Ross & Haley, 2004;Talbot et al, 1998). However, these programs are often designed for individuals with a variety of trauma experiences, and are not specific to women with childhood trauma histories.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Informed by having particular clinical and research interests in the trauma and dissociation field for well over a decade, 13 by contact with the literature of the field and with its writers, and by being heavily involved in establishing and directing a trauma and dissociation unit (with both inpatient and day hospital programmes), 14 my intention here is to briefly outline a personal but evolving conceptual and treatment model that takes account of Australian conditions.…”
mentioning
confidence: 99%